Andrographolide Ameliorate Rheumatoid Arthritis by Promoting the Development of Regulatory T Cells - Muhaimin Rifai'i (Journal of Tropical Life Science, 2010)
Andrographolide is important material present in Andrographis paniculata. This material can promote T cell to develop into regulatory T cell, CD4+CD25+. CD4+CD25+ regulatory T (Treg) cells, a component of the innate immune response, which play a key role in the maintenance of self-tolerance, have become the focus of numerous studies over the last decade. These cells have the potential to be exploited to treat autoimmune disease. In this experiment we showed that the induction of regulatory cells in vivo has a healing effect on mice model of rheumatoid arthritis (RA). RA mice which is intraperitoneally injected with Andrographis paniculata shows the effect of recovery. CD4+CD25+ regulatory T cells actively control the properties of other immune cells by suppressing their functional activity to prevent autoimmunity. In this experiment we showed that active compound from Andrographis paniculata namely andrographolide can induce active regulatory T cell that has an efficacy to cure rheumatoid arthritis in mice model. Keywords: Andrographolide; Andrographis sp; Regulatory T cells; Rheumatoid arthritis